Race, gender and the body in British immigration control : subject to examination / Evan Smith and Marinella Marmo. - Smith, Evan, 1981-; Marmo, Marinella (Migration, diasporas and citizenship., 2014)
This text analyses the practice of virginity testing endured by South Asian women who wished to enter Britain between the late 1960s and the early 1980s, and places this practice into a wider historical context. Using recently opened government documents the extent to which these women were interrogated and scrutinised at the border is uncovered.